ANALYSIS OF THE INFLUENCE OF CONTACT RATIO ON VIBRATION CHARACTERISTICS OF HERRINGBONE GEAR TRANSMISSION SYSTEM (MT) - YIN XunMin; JIA HaiTao; ZHANG RunBo; ZHANG XiJin (Jixie qiangdu)
The contact ratio is an important performance index in the design of gear transmission, and it directly affects the load-bearing capacity and transmission stability of herringbone gears. The requirements of contact ratio must be met when designing gear pairs. Firstly, the stiffness excitation and meshing impact excitation of herringbone gear system are introduced, and a bending-torsion-axis coupling model of a pair of herringbone gear transmission system is established by means of lumped-mass method. Then, the influence of contact ratio on time-varying meshing stiffness and meshing impact force is analyzed. Finally, the influence of contact ratio on the dynamic meshing performance of herringbone gear pairs is studied. The results show that when the contact ratio increases from 2.72 to 3.08, the peak-to-peak value of time-varying meshing stiffness is reduced from 4.653 3×10~8 N/mm to 3.229 9×10~8 N/mm, and the maximum meshing impact force is reduced from 2.23×10~3 N to 1.92×10~3 N, and dynamic meshing force curve of the gear pair becomes smooth, and the dynamic load factor is also reduced from 1.23 to 1.18. It is concluded that the increase of contact ratio can achieve the effect of system vibration reduction, noise reduction and transmission stability.